Vi polysaccharide and conjugated vaccines afford similar early, IgM or IgG-independent control of infection but boosting with conjugated Vi vaccines sustains the efficacy of immune responses - Jossi, Siân E.; Arcuri, Melissa; Alshayea, Areej; Persaud, Ruby R.; Marcial-Juárez, Edith; Palmieri, Elena; Di Benedetto, Roberta; Pérez-Toledo, Marisol; Pillaye, Jamie; Channell, Will M.; Schager, Anna E.; Lamerton, Rachel E.; et al. (Frontiers in Immunology, 2023)
Introduction Vaccination with Vi capsular polysaccharide (Vi-PS) or protein-Vi typhoid conjugate vaccine (TCV) can protect adults against Salmonella Typhi infections. TCVs offer better protection than Vi-PS in infants and may offer better protection in adults. Potential reasons for why TCV may be superior in adults are not fully understood. Methods and results Here, we immunized wild-type (WT) mice and mice deficient in IgG or IgM with Vi-PS or TCVs (Vi conjugated to tetanus toxoid or CRM197) for up to seven months, with and without subsequent challenge with Vi-expressing Salmonella Typhimurium. Unexpectedly, IgM or IgG alone were similarly able to reduce bacterial burdens in tissues, and this was observed in response to conjugated or unconjugated Vi vaccines and was independent of antibody being of high affinity. Only in the longer-term after immunization (>5 months) were differences observed in tissue bacterial burdens of mice immunized with Vi-PS or TCV. These differences related to the maintenance of antibody responses at higher levels in mice boosted with TCV, with the rate of fall in IgG titres induced to Vi-PS being greater than for TCV. Discussion Therefore, Vi-specific IgM or IgG are independently capable of protecting from infection and any superior protection from vaccination with TCV in adults may relate to responses being able to persist better rather than from differences in the antibody isotypes induced. These findings suggest that enhancing our understanding of how responses to vaccines are maintained may inform on how to maximize protection afforded by conjugate vaccines against encapsulated pathogens such as S. Typhi.